2008
DOI: 10.2337/dc07-1198
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Reduces Plasma Arginase Activity in Type 2 Diabetic Patients

Abstract: OBJECTIVE -We sought to determine whether dysregulation of arginine metabolism is related to insulin resistance and underlies impaired nitric oxide (NO) generation in type 2 diabetic patients.RESEARCH DESIGN AND METHODS -We measured plasma arginase activity, arginine metabolites, and skeletal muscle NO synthase (NOS) activity in 12 type 2 diabetic and 10 age-/BMI-matched nondiabetic subjects before and following a 4-h euglycemichyperinsulinemic clamp with muscle biopsies. Arginine metabolites were determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
72
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 39 publications
13
72
1
4
Order By: Relevance
“…Plasma arginase activity positively correlates with the severity of hyperglycemia in type 2 DM patients (20). In experimental DM animal models, aortic fibrosis is associated with increased arginase I and II protein levels and activity (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma arginase activity positively correlates with the severity of hyperglycemia in type 2 DM patients (20). In experimental DM animal models, aortic fibrosis is associated with increased arginase I and II protein levels and activity (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Arginase I is mainly cytoplasmic and II mitochondrial (29). Increases in arginase(s) activity correlate positively with the level of glycemic control and tissue fibrosis in DM patients (20,29,30). The role of arginases in regulating CF collagen synthesis in the setting of DM is yet to be explored.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, little is known regarding how changes in arginase activity are related to endothelial function among these patients. Kashyap et al 16 showed that patients with type 2 diabetes had increased plasma arginase activity in comparison with a control group. In addition, we recently demonstrated that arginase inhibition improves endothelial function in patients with type 2 diabetes and coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increased expression and/or activity of ARG have a deep impact on NOS efficiency. As an example, arginase activity is increased in type 2 diabetic subjects with impaired NOS activity, and such impairment correlates with the degree of hyperglycemia and is reduced by insulin (Kashyap et al, 2008). The problem is more interesting because results of experimental and clinical studies are quite controversial and can not definitely support relevant conclusions.…”
Section: Endothelial Vasomotion and The Exogenous Arginine Paradoxmentioning
confidence: 78%